Overview of Pediatric Hospitalization at Harapan Sehat Hospital in 2022 - notareza aulia, adico; Harahap, Laila Apriani Hasanah (LLDIKTI Wilayah 1, 2024)
In Indonesia, the number of hospitalizations in children reaches 2.3% of the total population in Indonesia. This study aims to see a picture of pediatric hospitalization at Harapan Sehat Hospital throughout 2022. This research is descriptive using medical record data in the hospital SIMRS application. It was found that female patients and the age range between 3 - 18 years were the most common. Likewise, typhoid fever cases are the most common diagnoses. This research is very useful to be one of the foundations of future National Health policies in Indonesia, especially in West Aceh. So that the health of Indonesian children can be healthier to welcome a better future for Indonesia.